Innovative training solutions for digitization - Maroso, Amy Lynn (Proceedings of the 5th ACM/IEEE Joint Conference on Digital Libraries : Denver, CO, USA, June 7-11, 2005 : digital libraries, cyberinfrastructure for research and education, 2005)
The benefits of digitizing library collections are important and diverse. Patrons outside traditional geographic boundaries can be served along side local patrons. Access to local history, a vibrant part of many library holdings, and original, rare, and/or valuable materials can be greatly expanded. However, the practice of digitization can fall short of its promise due to poor planning and a lack of digitization skills. Moreover, quality digitization training is not always accessible or feasible given the time, expense, and staff limitations for many institutions.The Basics and Beyond digitization training program offers a novel solution for this problem. Funded by an Institute of Museum and Library Services National Leadership grant and administered by the University of Illinois at Urbana-Champaign Library, the Illinois State Library, and the Illinois Heritage Association, Basics and Beyond offers three digitization training options to cultural heritage institutions: one-day on-site workshops, three-week online training, and three-week online training followed by a hands-on workshop.The content of the workshops provides participants with an overview of the digitization process. Topics presented include: project planning, equipment selection, metadata, and standards and best practices for digitizing materials. The online courses expand greatly on the material covered in the workshops and provide the participants with an in-depth look at the digitization process. They cover material such as using digitization as a preservation practice, selection of materials for digitization, project planning, metadata schemes, equipment needs, and standards and best practices. The online courses are accessible to anyone with a Web connection and provide institutions around the world with access to innovative digitization training. The online training is affordable to most organizations, and its asynchronous format allows librarians and staff to easily fit the course into their work schedules.The effectiveness of the workshops and courses has been determined by participant evaluations conducted both during the workshops and courses and several months after completion. Evaluations include pre- and post-course surveys, essay questions, and quizzes as well as follow-up telephone interviews conducted several months after course or workshop completion. Evaluations are designed to determine the quality of training and to what degree the training assisted in the implementation and practice of newly formed or revamped digital projects.Evaluation results have been overwhelmingly positive for all courses and workshops. Over 200 people have taken the one-day workshop. A nine-question pre-workshop quiz indicates that 80% of participants missed three or more questions before being exposed to the workshop material. As expected, participants score significantly higher when given the same quiz after the workshop-only 14% missed more than two questions. Over 130 people have taken one of the online courses. In addition to quizzes, objective evaluation is also done in the online courses and show that students are able to apply the information they learn in "real world" situations, such as equipment purchases and metadata creation. Evaluations and participants' comments indicate that the workshops and courses are highly successful and have accomplished the chief goal of the project-to educate cultural heritage institution professionals on the best practices for digitization to ensure the success and longevity of their digitized collections.